FACTORS THAT ARE ASSOCIATED WITH BURNOUT AMONG EMERGENCY MEDICINE RESIDENTS IN SAUDI ARABIA. A CROSS-SECTIONAL STUDY (CAHIERS MAGELLANES-NS, 2024)
Background: Burnout is a condition caused by prolonged exposure to an emotionally draining environment.  It is a source of concern among resident doctors, especially those working in the emergency department.  Herbert Freudenberger, a psychiatrist from the United States, created the term "burnout" in the seventies. Objectives: In this study, our intention was to identify the factors which might result in burnout in Saudi Arabian physicians working in emergency medicine.Methodology: In Saudi Arabia, emergency medicine residents were the subject for a cross-sectional questionnaire survey during 2023-2024. Staff members who have worked at the hospital for a minimum of six months were eligible to take part in the study. The data has been transferred, collected, and analyzed using SPSS. Raosoft website was used as a calculator for the sample size with confidence level 95%, and margin of error 5%. Results: As regard factors associated with burnout among emergency medicine residents, there were 57.9% reported having taken at least one sick leave during the last year and 74.9% admitted to taking short meals during work, which could potentially contribute to increased stress and burnout levels. Surprisingly, only 41.4% of respondents reported being on a regular exercise regimen, highlighting a potential area for intervention to promote overall well-being. The prevalence of sleep disturbances was notably high, with 71.6% of residents personally dealing with this issue. Regarding relation between feeling burnt out and sociodemographic characteristics, there were a statistically significant relation to age (p value=0.0001), region of residence (p value=0.0001), and marital status (p value=0.001). It also shows statistically insignificant relation to gender, nationality, being an emergency healthcare provider, and number of months the participant had been a resident.Conclusion: The findings indicated a high prevalence of burnout among participants, with various factors such as sick leave, short meal breaks, lack of exercise, and sleep disturbances contributing to increased stress and burnout levels. Sociodemographic characteristics like age, region of residence, and marital status were found to have a significant relation to burnout, highlighting the importance of considering these factors in addressing burnout among healthcare professionals.